filter
Patent Information
- Application Number
- CN202580023430.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-01
- Filing Date
- 2025-02-19
- Publication Date
- 2026-10-30
AI Technical Summary
[0016]本公开的过滤器能够降低气体通过时的压力损失。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to filters on which a metal-organic framework material is loaded onto a substrate. Background Technology
[0002] Metal-organic frameworks (MOFs) are also known as porous coordination polymers. They are materials that form porous structures through coordination bonds between metal ions and organic ligands. They are expected to be used in applications that utilize gas adsorption / desorption properties or in catalysts, etc.
[0003] For example, Patent Document 1 describes the use of a moisture-absorbing plate with a metal-organic framework material attached to its surface as a component of a humidity control device.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Korean Patent Publication No. 10-2020-0140435 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] Filters with metal-organic framework materials attached to the substrate surface are intended to minimize pressure loss when gas passes through the filter.
[0009] Therefore, the purpose of this disclosure is to provide a filter that can reduce pressure loss when gas passes through.
[0010] means for solving problems
[0011] The present disclosure, which has accomplished the above-mentioned task, is as follows.
[0012] [1] A filter comprising a metal-organic framework material loaded on a substrate, wherein, The substrate has one or more through holes. Air at a temperature of 78°C and a relative humidity of 3%–5% is directed along the axial direction of the through-hole at a wind speed of 45 m / s. 3 When the water flows through a filter that has undergone pretreatment (a) and water adsorption treatment (b) at a rate of / h, the following necessary conditions (R1) and (R2) are met: in the pretreatment (a), the filter is kept in air at a temperature of 80°C and a relative humidity of 3% to 5% for 30 minutes, and then kept in a sealed bag until the temperature reaches 25°C; in the water adsorption treatment (b), the filter that has undergone the pretreatment (a) is kept in air at a temperature of 20°C and a relative humidity of 70% for 600 seconds. Necessary condition (R1): Obtain graph P with time (seconds) on the horizontal axis and the cumulative desorption amount (g) relative to 1g of water in the filter on the vertical axis, and graph Q with time (seconds) on the horizontal axis and the temperature (°C) of the air downstream of the filter on the vertical axis. Determine the time t (seconds) at which the temperature of the air downstream of the filter reaches its lowest point in graph Q. The absolute value of the slope of the straight line connecting the point (t, P(t)) on graph P at time t to the origin is 9 × 10. -4 above; Required condition (R2): The cumulative desorption of water after 600 seconds is greater than 0.133g relative to 1g of filter.
[0013] [2] According to the filter described in [1], the cross-sectional area of the substrate section perpendicular to the axial direction of the through hole is 300 mm². 2 ~40000mm 2 , per 1cm 2 The cross-sectional area has 10 holes per cm. 2 ~150 holes / cm 2 .
[0014] [3] According to the filter described in [1] or [2], wherein the metal-organic framework material is composed of a metal element M and an organic ligand, wherein the metal element M is at least one selected from the group consisting of elements selected from the 4th to 6th periods and groups 3 to 12 of the long-period periodic table, Al, Ga, and In, and the organic ligand comprises elements selected from R(COO) - ) n At least one of the group consisting of carboxylate ions (where R is an n-valent group and n is an integer greater than 2).
[0015] Invention Effects
[0016] The filter disclosed herein can reduce pressure loss when gas passes through. Attached Figure Description
[0017] Figure 1 This is a schematic diagram showing the cross-sectional shape of the substrate used in the embodiments. Detailed Implementation
[0018] <Filter>
[0019] The filter disclosed herein has a metal-organic framework material loaded on a substrate. The substrate has one or more through-holes. Air at a temperature of 78°C and a relative humidity of 3%–5% is directed along the axial direction of the through-holes at a wind speed of 45 m / s. 3When the filter undergoes pretreatment (a) and water adsorption treatment (b) at a flow rate of / h, the following necessary conditions (R1) and (R2) are met: in the pretreatment (a), the filter is kept in air at a temperature of 80°C and a relative humidity of 3% to 5% for 30 minutes and in a sealed bag until the temperature reaches 25°C; in the water adsorption treatment (b), the filter that has undergone the pretreatment (a) is kept in air at a temperature of 20°C and a relative humidity of 70% for 600 seconds.
[0020] Necessary condition (R1): Obtain graph P with time (seconds) on the horizontal axis and the cumulative desorption amount (g) relative to 1g of water in the filter on the vertical axis, and graph Q with time (seconds) on the horizontal axis and the temperature (°C) of the air downstream of the filter on the vertical axis. Determine the time t (seconds) at which the temperature of the air downstream of the filter reaches its lowest point in graph Q. The absolute value of the slope of the straight line connecting the point (t, P(t)) on graph P at time t to the origin is 9 × 10. -4 above.
[0021] Required condition (R2): The cumulative desorption of water after 600 seconds is greater than 0.133g relative to 1g of filter.
[0022] By passing air at a temperature of 78°C and a relative humidity of 3%–5% through a filter that has undergone pretreatment (a) and adsorption treatment (b) at the aforementioned airflow rate, the moisture adsorbed by the filter can be desorbed. Necessary conditions (R1) and (R2) both describe the characteristics required for desorbing the moisture adsorbed by the filter. It is believed that in the filter of this disclosure, which satisfies necessary conditions (R1) and (R2), the MOF is loaded onto the substrate in a dispersed and non-agglomerated state. At locations where MOF agglomerates, the filter readily adsorbs moisture from the surrounding environment (e.g., temperature of 10°C–40°C, relative humidity of 5%RH–80%RH; or temperature of 20°C–35°C, relative humidity of 20%RH–50%RH), easily forming water droplets. However, it is believed that in the filter of this disclosure, which satisfies necessary conditions (R1) and (R2), the areas where such water droplets accumulate can be reduced, thus reducing pressure loss.
[0023] When the moisture adsorbed by the filter begins to desorb, the temperature of the air downstream of the filter decreases; when desorption is essentially complete, the temperature of the air downstream of the filter begins to rise. That is, the time point T in Figure Q above where the temperature of the air downstream of the filter is lowest refers to the time point when the adsorbed moisture in adsorption treatment (b) has essentially desorbed. Therefore, the absolute value of the slope of the straight line specified in necessary condition (R1) (hereinafter referred to as slope k) is 9 × 10⁻⁶. -4 This means that the water adsorbed by the filter can be rapidly desorbed (hereinafter referred to as desorption rate characteristics (1)).
[0024] In addition, under the necessary condition (R2), the cumulative desorption of water after 600 seconds is more than 0.133g relative to 1g of filter, which means that the absolute amount of water that the filter can desorb is large (hereinafter referred to as the desorption characteristic (2)).
[0025] The desorption rate characteristic (1) and the desorption amount characteristic (2) are both determined by allowing air at a temperature of 78°C and a relative humidity of 70% to move along the axial direction of the aforementioned through-hole at a wind speed of 45m. 3 The test was conducted on the filter of this disclosure, which had undergone the above-described pretreatment (a) and water adsorption treatment (b), and the flow rate was measured.
[0026] Specifically, air at a temperature of 78°C and a relative humidity of 70% (air on the inflow side) is prepared and passed through a filter that has undergone pretreatment (a) and water adsorption treatment (b). The temperature X (°C) and relative humidity Y (%) of the air downstream of the filter (air on the outflow side) are measured. For both the inflow and outflow air, the saturated water vapor pressure is calculated based on the temperature values using the following formula (1). The temperature X (°C) and relative humidity Y (%) of the air downstream of the filter can be measured at a distance of 0–30 cm from the downstream surface of the filter along the axial direction of the through-hole.
[0027]
[0028] In the above formula, T is the air temperature (°C), and e ω Saturated water vapor pressure (g / m 2 ).
[0029] Next, based on the relative humidity (%) and the saturated water vapor pressure (g / m³) calculated above... 2 Based on the following formula (2), the absolute amount of water contained in 1 kg of air (g / kg) can be calculated.
[0030] Relative humidity (%) = 100 × {water vapor pressure of given air (g / m³)} 2 ) / {saturated water vapor pressure (g / m 2 )} ……(2)
[0031] For both the inflow and outflow air, calculate the absolute amount of moisture in 1 kg of air. Then, calculate the absolute value (g / kg) of the difference between the absolute amount of moisture in 1 kg of inflow air and the absolute amount of moisture in 1 kg of outflow air. Since the temperature and humidity on the outflow side change over time, measurements are taken. The absolute values of these subtractions are accumulated and multiplied by the total volume of air passing through the filter (kg). This allows for an estimation of the amount of moisture desorbed from the filter.
[0032] The upper limit of the absolute value of the slope k is, for example, 1.5 × 10⁻⁶. -3 The preferred value is 1.0 × 10⁻⁶. -3 The following is more preferably 9.5×10 -4 The absolute value of the slope k is preferably 9 × 10⁻⁶. -4 ~1.5×10 -3 More preferably 9×10 -4 ~1.0×10 -3 Further preferred is 9×10 -4 ~9.5×10 -4 .
[0033] Relative to 1g of filter, the cumulative desorption amount of water after 600 seconds is preferably 0.15g or more, more preferably 0.16g or more, even more preferably 0.17g or more, and the upper limit can be, for example, 0.23g. Relative to 1g of filter, the cumulative desorption amount of water after 600 seconds is preferably 0.133g to 0.23g, more preferably 0.15g to 0.23g, even more preferably 0.16g to 0.23g, and even more preferably 0.17g to 0.23g.
[0034] In this disclosure, the preferred slope k is 9 × 10 -4 ~1.5×10 -3 Furthermore, the cumulative desorption of water after 600 seconds is 0.15g to 0.23g, and more preferably, the slope k is 9×10. -4 ~1.0×10 -3 Furthermore, the cumulative desorption of water after 600 seconds was 0.16 g to 0.23 g, and the slope k was further optimized to be 9 × 10⁻⁶ g. -4 ~9.5×10 -4 Furthermore, the cumulative desorption of water after 600 seconds was 0.17g to 0.23g.
[0035] The MOF loading per unit area of the filter is, for example, 65 g / m². 2 The above is preferably 70g / m 2 The above, more preferably 75g / m 2In addition, it can be 120g / m 2 The MOF loading is preferably 0.40g or more per 1g of filter, with an upper limit of, for example, 0.7g or less. The MOF loading per unit area of the filter is, for example, 65g / m². 2 ~120g / m 2 Preferably 70g / m 2 ~120g / m 2 More preferably 75g / m 2 ~120g / m 2 The MOF loading is preferably 0.40g to 0.7g per 1g of filter.
[0036] When the face wind speed is 1.0 m / s, the pressure loss measured according to the principles of the embodiments described later is preferably 25 Pa or less, more preferably 25 Pa to 10 Pa, and even more preferably 22 Pa to 10 Pa. Furthermore, when the face wind speed is 1.5 m / s, the pressure loss is preferably 42 Pa or less, more preferably 42 Pa to 20 Pa, and even more preferably 35 Pa to 20 Pa.
[0037] Metal-Organic Framework Materials
[0038] MOFs are composed of metals and organic ligands. The metallic element M constituting the MOF can be, for example, at least one element selected from the group consisting of elements in periods 4 to 6 and groups 3 to 12 of the long-period periodic table, Al, Ga, and In. Preferably, it can be at least one element selected from the group consisting of Al, Ga, In, Ti, Zr, Hf, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, with Al being particularly preferred.
[0039] It should be noted that when the composition of the loaded MOF is unknown, the filter can be cut at a cross-section where the substrate and the MOF loaded on the substrate can be observed, and the concentration distribution in the depth direction can be measured by SEM-EDX or similar methods to identify the metal element M of the MOF. In the filter disclosed herein, the MOF is loaded on the surface of the substrate; therefore, in the concentration distribution in the depth direction, the element with a concentration near the filter surface greater than that inside the substrate is the metal element of the MOF.
[0040] As an organic ligand, it is preferred to contain R(COO) selected from it. - ) n(R is an n-valent group, where n is an integer of 2 or more) represents at least one of the group consisting of carboxylate ions (carboxylate groups). R is preferably an aliphatic chain hydrocarbon group, an aliphatic cyclic hydrocarbon group, an aliphatic heterocyclic hydrocarbon group (a group in which one or more carbon atoms of an aliphatic cyclic hydrocarbon group are replaced by heteroatoms), an aromatic hydrocarbon group, an aromatic heterocyclic hydrocarbon group (a group in which one or more carbon atoms of an aromatic hydrocarbon group are replaced by heteroatoms), and most preferably an aromatic hydrocarbon group. The number of carbon atoms in R is preferably 2 to 30, more preferably 4 to 24, and even more preferably 6 to 18. n is preferably 2 or more and 4 or less, more preferably 2 or more and 3 or less, and most preferably 2.
[0041] The aforementioned aliphatic chain hydrocarbon group, aliphatic cyclic hydrocarbon group, aliphatic heterocyclic hydrocarbon group, aromatic hydrocarbon group, and aromatic heterocyclic hydrocarbon group may further include one or more functional groups X, wherein the functional group X is -OH and / or -NH2.
[0042] Aliphatic chain hydrocarbon groups can be straight-chain or branched, and can be saturated or unsaturated. Examples of aliphatic chain hydrocarbon groups include those obtained by removing n hydrogen atoms from ethane, ethylene, acetylene, butane, butene, or hexane.
[0043] Examples of aliphatic cyclic hydrocarbon groups include groups obtained by removing n hydrogen atoms from cyclopropane, cyclobutane, cyclohexane, cyclooctane, norbornene, or adamantane.
[0044] Examples of aliphatic heterocyclic hydrocarbon groups include groups obtained by removing n hydrogen atoms from pyrrolidine, piperidine, piperazine, or morpholine.
[0045] The preferred range of the number of carbon atoms in the aromatic hydrocarbon group is 6 or more and 30 or less, 6 or more and 24 or less, 6 or more and 18 or less, 6 or more and 12 or less, and 6 or more and 10 or less. Specifically, the aromatic hydrocarbon group is a group obtained by removing n (preferably 2 or 3) hydrogen atoms from benzene or biphenyl, especially a group obtained by removing n (preferably 2 or 3) hydrogen atoms from benzene.
[0046] The aromatic hydrocarbon group is preferably any one of the following formulas (A-1) to (A-9), more preferably any one of formulas (A-1) to (A-3), and even more preferably formula (A-2). In the following formulas (A-1) to (A-9), Indicates the bonding site.
[0047]
[0048] In the above formulas (A-1) to (A-9), at least one of the hydrogen atoms bonded to the carbon atom can be replaced by -OH and / or -NH2, and the hydrogen atoms bonded to the carbon atom may also be unsubstituted.
[0049] As aromatic heterocyclic hydrocarbon groups, examples include: pyrrole, pyrazole, imidazole, thiazole, etc. A group obtained by removing n hydrogen atoms from azole, pyridine, pyrimidine, pyridazine, pyrazine, or triazine.
[0050] The metal and organic ligand constituting the MOF can be appropriately combined within the aforementioned preferred range. For example, the preferred metal is at least one selected from the group consisting of Al, Ga, In, Ti, Zr, Hf, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, and the preferred organic ligand is R(COO) - ) n Wherein, R is an aromatic hydrocarbon group, n is a MOF of 2 or 3 carboxylate ions, more preferably Al metal, and the organic ligand is R(COO) - ) n , where R is any one of the above formulas (A-1) to (A-3), and n is a MOF of 2.
[0051] The molar ratio (metal ion / organic ligand) of the metal ion (in many cases, a total stoichiometry) to the organic ligand (in many cases, a total stoichiometry) is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, particularly preferably 0.9 or more, and preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2.5 or less. This molar ratio is preferably 0.1 to 5, more preferably 0.3 to 4, even more preferably 0.5 to 3, and even more preferably 0.9 to 2.5.
[0052] The organic ligands constituting MOFs are the aforementioned R(COO-). n In the case of the carboxylate ion shown, relative to 1 mole of R(COO-) n The amount of metal constituting the MOF is preferably 0.8×n moles to 1.5×n moles, more preferably 0.8×n moles to 1.2×n moles.
[0053] The preferred BET specific surface area of MOF is, for example, 450 m². 2 / g~800m 2 / g, more preferably 500m 2 / g~750m 2 / g, further preferably 530m 2 / g~700m 2 / g, preferably 580m 2 / g~700m 2 / g.
[0054] MOFs can be manufactured using conventional methods, which involve reacting a metal compound containing metal ions constituting the MOF with an organic compound that serves as an organic ligand constituting the MOF in a solvent. More specifically, it is preferable to prepare a solution B obtained by completely dissolving the metal compound containing the metal ions and a solution A obtained by completely dissolving the organic compound that serves as the organic ligand, and to add either solution dropwise to the other to allow them to react.
[0055] The metal compound containing the metal ion constituting the MOF is preferably a sulfate, nitrate, acetate, chloride, bromide, or alkoxide of the metal, more preferably a sulfate. The organic compound that serves as the organic ligand constituting the MOF is preferably composed of R(COOH). n (R and n are the same as above) represent polycarboxylic acids.
[0056] The preferred solvents are water, alcohols such as methanol and ethanol, and amides such as N,N-dimethylformamide. Only one solvent may be used, or a mixture of two or more may be used. Particularly when a metal compound containing metal ions constituting the MOF reacts with an organic compound that becomes an organic ligand constituting the MOF in the presence of water as a solvent, the reaction is preferably carried out in the presence of a tertiary amine such as triethylamine.
[0057] After the reaction is complete (preferably after the dropwise addition is complete), the product is subjected to at least one of the following at a temperature of room temperature (e.g., 25°C) to 200°C for about 5 minutes to about 100 hours: reflux, stirring, and standing. The reaction product is then separated from the solvent by centrifugation or filtration, washed, and dried to obtain the target MOF.
[0058] <Substrate>
[0059] Regarding the composition of the substrate, examples include: a substrate with at least a metal, metal oxide, etc., on the surface, preferably a substrate with at least a silicate on the surface, wherein the silicate may contain at least one of Ca, Mg, Fe, Na and Al.
[0060] The substrate has one or more through holes, and preferably has a columnar shape. Columnar shapes are preferably cylindrical, prismatic, or elliptical. The number of through holes is preferably two or more. Regarding the shape of the holes in a cross-section perpendicular to the axial direction, in addition to circles, examples include polygons such as triangles, quadrilaterals, or hexagons, and also shapes with rounded vertices.
[0061] The cross-sectional area of the substrate section perpendicular to the axis of the through hole is preferably 300 mm². 2 ~40000mm 2 More preferably 500mm 2 ~35000mm2 Further preferred is 5000mm 2 ~30000mm 2 A further preferred size is 10000mm. 2 ~25000mm 2 The length of the substrate (axial length of the through hole) is preferably 10 mm to 200 mm, more preferably 20 mm to 150 mm.
[0062] Per 1cm of the substrate cross section perpendicular to the axis of the through hole 2 The preferred cell count (number of pores) per cm² is 10 pores / cm². 2 ~150 holes / cm 2 More preferably, 20 holes / cm 2 ~100 holes / cm 2 Further preferred is 30 holes / cm 2 ~80 holes / cm 2 .
[0063] The area (average value) of a single hole in a substrate cross-section perpendicular to the axis of the through hole is preferably 0.5 mm². 2 ~10mm 2 More preferably 1mm 2 ~8mm 2 More preferably 2mm 2 ~6mm 2 .
[0064] The thickness of the inner wall separating the pores is preferably 10 μm to 1000 μm, more preferably 50 μm to 500 μm, and even more preferably 100 μm to 300 μm. The thickness of the outer wall of the substrate is also preferably within the above range.
[0065] The total surface area of the inner and outer surfaces of the substrate, including the inner and outer walls, is preferably 0.01 m². 2 ~2m 2 More preferably 0.1m 2 ~1.8m 2 More preferably 0.5m 2 ~1.5m 2 .
[0066] In this disclosure, the cross-sectional area of the substrate section perpendicular to the axis of the through hole is preferably 300 mm². 2 ~40000mm 2 And every 1cm 2 The cross-sectional area has 10 holes per cm. 2 ~150 holes / cm 2More preferably, the cross-sectional area of the substrate section perpendicular to the axis of the through hole is 500 mm². 2 ~35000mm 2 And every 1cm 2 The cross-sectional area has 20 holes per cm. 2 ~100 holes / cm 2 Furthermore, the cross-sectional area of the substrate section perpendicular to the axis of the through hole is preferably 10000 mm². 2 ~25000mm 2 And every 1cm 2 The cross-sectional area has 30 holes per cm². 2 ~80 holes / cm 2 .
[0067] <Filter Manufacturing Method>
[0068] The filter disclosed herein can be manufactured by immersing a substrate in a slurry containing MOF, lifting it out, and then drying it. Particularly important is the appropriate adjustment of the MOF concentration and the number of coatings in the slurry, and the adjustment of the MOF loading per unit area of the substrate. More specifically, it is preferable to perform any of the following operations: coating the substrate once with a slurry having a high MOF concentration (e.g., 20% to 40% by mass) and drying it. Furthermore, the preferred range for the MOF loading per unit area of the substrate is as described above. The MOF loading per unit area of the substrate can be adjusted by adjusting the immersion time of the substrate in the MOF-containing slurry, or by adjusting the slurry volume by applying vibration to the substrate after immersion in the MOF-containing slurry.
[0069] In addition to MOF, the slurry preferably contains solvent, emulsifier, dispersant, and pH adjuster. Furthermore, the pH of the slurry is preferably 4 to 5.
[0070] The drying temperature and time of the substrate after impregnation with the MOF-containing slurry are, for example, 30°C to 600°C and 1 hour to 24 hours.
[0071] <Application>
[0072] The filter disclosed herein is suitable for the adsorption and removal of gases and organic molecules, and can also be used as a component of a replaceable housing, humidification device, etc. Examples of gases include: water (water vapor), carbon dioxide, hydrogen, carbon monoxide, oxygen, nitrogen, hydrocarbons with 1 to 4 carbon atoms, noble gases, hydrogen sulfide, ammonia, sulfur oxides, nitrogen oxides, siloxanes, etc. Examples of organic molecules include: hydrocarbons with 5 to 8 carbon atoms, alcohols with 1 to 8 carbon atoms, aldehydes with 1 to 8 carbon atoms, carboxylic acids with 1 to 8 carbon atoms, ketones with 1 to 8 carbon atoms, amines with 1 to 8 carbon atoms, esters with 1 to 8 carbon atoms, amides with 1 to 8 carbon atoms, etc. It should be noted that the above-mentioned organic molecules may contain aromatic rings.
[0073] Example
[0074] The present disclosure is further illustrated below with examples. The present disclosure is not limited to the examples described below, and may be implemented with appropriate modifications that conform to the foregoing and hereinafter the spirit of the description, all of which are included within the technical scope of the present disclosure.
[0075] [Determination of BET surface area of MOF]
[0076] Since the adsorption area occupied by nitrogen molecules is known in advance, the amount of gas molecules adsorbed only on the sample surface is measured, and the surface area of the MOF sample is determined according to the BET adsorption isotherm.
[0077] Sample preparation: In order to remove water from the sample, it was heated overnight under reduced pressure at 200°C and below 10 Pa.
[0078] Device: BELSORP-mini manufactured by MicrotracBEL Co., Ltd.
[0079] Preprocessing conditions: (ai) Place a volume-reducing glass rod (for standard sample tubes) in a standard sample tube and seal it using a quick seal. Prepare the sample to be measured for this set of sample tubes (maximum of 3 samples per measurement), connect it to the pretreatment device (BELPREP VACII), purge the air from the sample tubes, and then introduce N2 gas (purity ≥ 99.999%) to atmospheric pressure.
[0080] (a-ii) Then, the sample tube is removed from the pretreatment machine and its weight is measured three times using a precision balance (displaying at least four decimal places) to obtain its average value (W1). An ion generator is used to eliminate the influence of static electricity when using the precision balance.
[0081] (a-iii) Measure about 50 mg of the sample to be measured on weighing paper and place the sample directly into the spherical part at the bottom of the standard sample tube using a long-necked funnel.
[0082] (a-iv) Return the glass rod to the sample tube, seal it with a quick seal, and then measure the overall weight once to temporarily confirm the amount of sample added.
[0083] (av) Connect the sample tube containing the sample to the pretreatment device and vent the air from the sample tube.
[0084] (a-vi) After the pressure inside the sample tube is sufficiently low, heating begins (with continued evacuation).
[0085] Measurement conditions: (bi) After the pretreatment (vacuum heating) is completed, the sample tube is kept under reduced pressure to dissipate heat. After reaching room temperature, N2 gas is introduced to atmospheric pressure and removed from the device.
[0086] (b-ii) The weight of the sample tube containing the pretreated sample was measured three times using a precision balance, and the average value (W2) was obtained. W2-W1 was calculated to obtain the weight of the sample.
[0087] (b-iii) Input the sample weight, information on N2 gas at liquid nitrogen temperature (second virial coefficient, etc.) into the measurement software, input the relative pressure to be measured, and press the measurement start button.
[0088] Then, following the software instructions, set up the Dewar flask filled with liquid nitrogen and the sample tube, and then perform the measurement.
[0089] MOF loading (g / m³) 2 [Determination of]
[0090] The weight of the filter substrate before and after MOF loading was measured separately. The weight difference was then calculated based on the surface area (m²) of the substrate. 2 ) Calculate the MOF load per unit area of the filter.
[0091] [Determination of desorption properties]
[0092] The filters manufactured in the examples and comparative examples were subjected to a pretreatment (a) of maintaining air at 80°C and 3%–5% relative humidity for 30 minutes, and then maintaining it in a sealed bag until the temperature reached 25°C. The weight was quickly measured. Next, the device was stabilized at 20°C and 70% relative humidity, and the filters that had undergone the pretreatment (a) were subjected to a water adsorption treatment (b) of maintaining air at 20°C and 70% relative humidity for 600 seconds. The weight was quickly measured, and the adsorbed filters were placed in an aluminum zipper bag. Next, the device was stabilized to ensure a stable supply of air at 78°C and 3%–5% relative humidity, and the air at 78°C and 3%–5% relative humidity was supplied axially along the through-hole at a wind speed of 45 m / s. 3 The airflow rate is / h, and the temperature and relative humidity of the air passing through the filter are measured over time. Measurements continue until the changes in temperature and humidity of the air exiting the filter disappear.
[0093] For the air flowing in and out, calculate the absolute amount of moisture in 1 kg of air according to equations (1) and (2) above. Subtract the absolute amount of moisture in 1 kg of air flowing out from the absolute amount of moisture in 1 kg of air flowing in (the negative value) and sum the results. Multiply this sum by the total amount of air passing through the filter (kg) to calculate the amount of moisture desorbed (g). Obtain graph P with time (seconds) as the horizontal axis and the vertical axis set to the cumulative desorption amount (negative value) per 1g of filter, and graph Q with time (seconds) as the horizontal axis and the temperature (°C) of the air downstream of the filter as the vertical axis. Determine the time t (seconds) at which the temperature of the air downstream of the filter is lowest in graph Q. Calculate the absolute value of the slope of the straight line connecting the point (t, P(t)) on graph P at time t to the origin, and calculate the absolute value of the cumulative desorption amount (per 1g of filter) after 600 seconds.
[0094] [Determination of pressure loss]
[0095] A filter manufactured in the same manner as in the examples and comparative examples was installed in the pressure loss measuring device in a cross-section perpendicular to the axial direction of the through-hole, such that no gap was formed between the filter and the pressure loss measuring device. The exhaust fan was operated, and the pressure difference at a set nozzle was measured using a differential pressure gauge and converted into airflow. Furthermore, the airflow was converted into face velocity based on the ventilation area of the sample, and the resistance value (pressure loss, unit: Pa) was measured. The frequency of the exhaust fan was varied, and the resistance value (pressure loss, unit: Pa) was measured at four different airflow rates. The resistance value for each face velocity was calculated and plotted, and the result was obtained using Y=aX. b Using the exponential approximation of (X is the face wind speed (m / s) and Y is the pressure loss (Pa)), the pressure loss at face wind speeds of 1.0 m / s and 1.5 m / s is calculated respectively.
[0096] It should be noted that in the measurement of pressure loss, a cross-sectional area of approximately 53600 mm² was used. 2 The filter was manufactured in the same manner as described in the examples and comparative examples below, except that it used a substrate with approximately 61 layers and a cylindrical shape. Furthermore, the ambient temperature during the manufacture of the filter used for pressure loss measurement and until the pressure loss measurement was 20°C to 35°C, and the relative humidity was 20%RH to 50%RH.
[0097] (Preparation Example 1-1: Preparation of Metal-Organic Framework Material 1)
[0098] In a 13L autoclave, 3.91 mol of isophthalic acid and 3200 mL of DMF (N,N-dimethylformamide) were mixed at 25°C until completely dissolved to obtain solution A. Separately, solution B was prepared by mixing 3.75 mol of Al2(SO4)3·nH2O (n=14–18) and 4800 mL of deionized water until completely dissolved. Solution B was added dropwise to solution A over 45 minutes at 25°C. The resulting mixture was then refluxed at 135°C for 12 hours to obtain a suspension. This suspension was pressure filtered, and the precipitated solids were washed three times with 1500 mL of DMF and three times with 1500 mL of methanol. The resulting filter cake was dried in a vacuum drying oven at 50°C for 3 hours to obtain 865.23 g of the product (MOF1) (yield 94%). It should be noted that the BET specific surface area of MOF1 is 612 m². 2 / g.
[0099] (Preparation Examples 1-2: Preparation of Metal-Organic Framework Material 2)
[0100] Solution A was prepared in a 13L autoclave by dissolving 3.50 mol of isophthalic acid and 9.94 mol of triethylamine in 8060 mL of water. Solution B was prepared by mixing 2.54 mol of Al2(SO4)3·nH2O (n=14~18) with 540 mL of ion-exchanged water and dissolving it completely. Solution B was added dropwise to solution A at 25°C over 45 minutes. Then, the mixture was refluxed at 100°C for 12 hours to obtain a suspension. The suspension was then pressure filtered, and the precipitated solid was washed twice with 2000 mL of ion-exchanged water and twice with 2000 mL of methanol. The resulting filter cake was dried in a vacuum drying oven at 100°C for 6 hours to obtain 721.97 g of the product (MOF2) (yield 97.9%). It should be noted that the BET specific surface area of MOF2 is 660 m². 2 / g.
[0101] (Preparation Example 2: Preparation of a slurry containing a metal-organic framework material)
[0102] The metal-organic framework material obtained in Preparation Example 1-1 or Preparation Example 1-2 was mixed with a solvent to prepare a slurry containing the metal-organic framework material with a pH of 4 to 5.
[0103] Example 1
[0104] A 130mm × 130mm × 30mm long substrate containing wollastonite was immersed in a slurry prepared by mixing metal-organic framework materials in an amount that reaches the concentration described in Table 1 below, in accordance with the method of Preparation Example 2. The substrate was then lifted out and dried to produce a filter with metal-organic framework materials loaded on the substrate.
[0105] The above-mentioned substrate is made of having Figure 1 The corrugated core 1 shown is composed of a face paper 2 and a back paper 3 that are attached to the core 1. The corrugation height h of the core is about 1.7 mm and the corrugation width p (pitch) is about 2.7 mm. The number of layers is 76.
[0106] Example 2, Comparative Examples 1 and 2
[0107] The substrate of the dimensions listed in Table 1 was immersed in a slurry prepared with the MOF concentration in the slurry listed in Table 1, lifted out, and then dried (first time). The second, third, and fourth times were then repeated with the concentration listed in Table 1. Otherwise, the operation was the same as in Example 1, thereby producing a filter with metal-organic framework material loaded on the substrate.
[0108] The conditions and results of the embodiments and comparative examples are shown in Tables 1 and 2.
[0109] [Table 1]
[0110] [Table 2]
[0111] Label Explanation
[0112] 1...core
[0113] 2... tissues
[0114] 3...lining paper
[0115] h……corrugated height of the core
[0116] p... the corrugated width (spacing) of the core.
Claims
1. A filter comprising a metal-organic framework material loaded on a substrate, wherein, The substrate has one or more through holes. Air at a temperature of 78°C and a relative humidity of 3%–5% is directed along the axial direction of the through-hole at a wind speed of 45 m / s. 3 When the water flows through a filter that has undergone pretreatment (a) and water adsorption treatment (b) at a rate of / h, the following necessary conditions (R1) and (R2) are met: in the pretreatment (a), the filter is kept in air at a temperature of 80°C and a relative humidity of 3% to 5% for 30 minutes, and then kept in a sealed bag until the temperature reaches 25°C; in the water adsorption treatment (b), the filter that has undergone the pretreatment (a) is kept in air at a temperature of 20°C and a relative humidity of 70% for 600 seconds. Necessary condition (R1): Obtain graph P with time (seconds) on the horizontal axis and the cumulative desorption amount (g) relative to 1g of water in the filter on the vertical axis, and graph Q with time (seconds) on the horizontal axis and the temperature (°C) of the air downstream of the filter on the vertical axis. Determine the time t (seconds) at which the temperature of the air downstream of the filter reaches its lowest point in graph Q. The absolute value of the slope of the straight line connecting the point (t, P(t)) on graph P at time t to the origin is 9 × 10. -4 above; Required condition (R2): The cumulative desorption of water after 600 seconds is greater than 0.133g relative to 1g of filter.
2. The filter according to claim 1, wherein, The cross-sectional area of the substrate section perpendicular to the axial direction of the through hole is 300 mm². 2 ~40000mm 2 , per 1cm 2 The cross-sectional area has 10 holes per cm. 2 ~150 holes / cm 2 .
3. The filter according to claim 1 or 2, wherein, The metal-organic framework material is composed of a metal element M and an organic ligand. The metal element M is selected from at least one element chosen from the group consisting of elements in periods 4 to 6 and groups 3 to 12 of the long-period periodic table, Al, Ga, and In. The organic ligand comprises elements selected from R(COO) - ) n At least one of the group consisting of carboxylate ions (where R is an n-valent group and n is an integer greater than 2).
Citation Information
Patent Citations
Dehumidifying apparatus and method using thermoelectric module
KR1020200140435A
